The Adverse Effects of Recruiting Non-Expert Officials : A Study of The Predictive Hadith: Entrusting Affairs To Non-Experts - Sagirah, Sitti (LPPM IAIN Sultan Amai Gorontalo, 2023)
This article elaborates and analyzes the meaning of the predictive Hadith about Handing over affairs to non-experts, then criticizes its authenticity and analyzes its content and implementation in the present context. The method used is the tahli>li method and textual, intertextual, and contextual interpretation techniques with a multidisciplinary approach. Before criticizing the authenticity of the Hadith based on the rules of hadith validity, first, perform takhri>j al-hadi>s by using the keyword d uyi'at al-ama>nat. After recognizing the quality of the traditions traced in this study as sahih traditions, a study of ma'a>ni> al-hadith followed. The results show that the Prophetic tradition is of sahih quality. This study shows that the predictive hadith